EVEREST Trial 2-Year Results Show Stability of Percutaneous MV Repair between Years 1 and 2 - Feldman, Ted (MD Conference Express, 2011)
The 2-year results from the Endovascular Valve Edge-to-Edge Repair trial [EVEREST II; NCT00209274] showed that percutaneous mitral valve repair is safe and durable with measurable clinical benefits and is a therapeutic option for select patients with significant mitral regurgitation [Feldman T et al. N Engl J Med 2011].